Suburbia on the box (2013)
Th is chapter addresses the subject of how suburbia is pictured on television: both underwent a growth period in the twentieth century. Indeed at the same time as marketing campaigns for new suburban housing the television was, alongside the labour-saving devices of refrigerator and washing machine, one of the luxuries that was dangled at new suburban dwellers to furnish their home with aft er the shackles of post-war austerity were being shaken off . Spigel ( 2001b :388) has looked at early print advertisements for television sets and fi nds that these off ered and fed into ‘utopian visions and middle-class anxieties about the future of family life and in particular, the future of gender and generational relations in the home’. Th e ideal lifestyle presented in many examples depicts families around the box which is positioned hearth-like as the focal point of the room emitting a rosy glow. From Queen Elizabeth II’s coronation when whole British streets seeking a sighting of this hitherto unprecedented spectacle would cram into the homes of those, at the time rare, families who possessed a set, to its present near-universal penetration (with albeit fragmented viewing habits) via the era of mass audiences and prime time, television has attained a ubiquity and attendant promise of escapism to a far greater degree than the more discerning and arguably stratifi ed or at least more specialized publics for literature, cinema and music.